The cooperation of the population of Isan in solid waste management: an investigation undertaken at the Isan sub –district municipality of Muang district Buriram province - Thiangtrong, Patama; Bouphan, Prachak (Asia-Pacific Journal of Science and Technology, 2017)
This study was cross sectional descriptive and the purpose was to investigate people’s participation and factors influencing in waste management in municipal area of Isan subdistrict, Muang district, Buriram province. The number of studied subjects was 323, which were systemalically selected from the total population of 18,146 during January1-31, 2011. SPSS for Windows was used for analyzing data. Percentage, mean, standard deviation, median, Pearson product-moment coefficient correlation and stepwise multiple regression analysis were employed to analyze data. The results were shown that people’s participation in waste management was moderate at 2.68 (S.D.=0.66) and position in the community as well as amount of waste in household and social factors have related with participation. Factors effecting people’s participation in waste management were to be informed the knowledge of waste management and to support by the municipality. They could be taken to make forecast of people’s participation in waste management in municipal area of Isan sub-district, Muang district, Buriram province – at 57.10%. Most found problems were social factors.